Sustainable, faster and more productive aquaculture of catfish.
With 57 percent of EU consumption being imported from China and Southeast Asia, European producers are facing fierce competition only aggravated by depleting fish stocks. Catfish production for instance is overrun by pangasius imports, and more efficient production technologies for aquaculture are desparately needed. The SILGEN project promises just that.